THE EFFECT OF HALAL AWARENESS AND PERCEIVED QUALITY ON THE DECISION TO PURCHASE SNACKS WITH BRAND IMAGE AS A MEDIATION VARIABLE - Juniwati, Juniwati; Maghribi, Rizqi (Fakultas Ekonomi dan Bisnis, UNTAN, 2022)
The global Islamic market may be due to the fact that the growth rate of the Muslim population is almost double that of the Christians and is expected to double in the span of four decades. These conditions make many companies currently target sales to the Muslim consumer segment to take advantage of the available opportunities. This study aims to determine the effect of halal awareness and perceived quality on Muslim millennial purchasing decisions through brand image as an intervening variable. The study used a causal associative method with a quantitative approach. The sample used was 250 respondents from Muslim millennials throughout Indonesia and had consumed snacks. The hypothesis was tested using a Structural Equation Model (SEM) based on Partial Least Square (PLS). Based on the test results, it is known that halal awareness and perceived quality affect brand image and purchasing decisions. The brand image was found to mediate the variables of halal awareness and perceived quality of purchasing decisions. The implication of this research for marketers and producers of snack foods is as input in designing a more appropriate marketing strategy supported by Muslim millennial halal awareness.JEL : E24, E220, I25.